2022
DOI: 10.1039/d1tc06103h
|View full text |Cite
|
Sign up to set email alerts
|

Molecular engineering of benzothiadiazole-based polymers: balancing charge transport and stretchability in organic field-effect transistors

Abstract: Fluorination is a common strategy for improving the electronic properties of π-conjugated materials, and this has shown to be important for applications in organic electronics, especially for the fabrication of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 50 publications
0
25
0
Order By: Relevance
“…In comparison with P1 and P2 , copolymer P3 exhibited stabilized HOMO energy levels due to the long straight alkoxy chain substitution on the bithiazole. 30 The planarity of the polymer backbone via intramolecular non-covalent interactions can be beneficial in OFET devices.…”
Section: Resultsmentioning
confidence: 99%
“…In comparison with P1 and P2 , copolymer P3 exhibited stabilized HOMO energy levels due to the long straight alkoxy chain substitution on the bithiazole. 30 The planarity of the polymer backbone via intramolecular non-covalent interactions can be beneficial in OFET devices.…”
Section: Resultsmentioning
confidence: 99%
“…7b. Another factor to be considered is the effect of fluorination on the mechanical and electrical properties of conjugated polymers, which was also evaluated by Ocheje et al 112 Their work demonstrated the relationship between a series of fluorination and/or alkylation with benzothiadiazole-based polymer in the solid-state. The crack onset strains of the prepared polymers ranged from as low as 10% for the polymer containing only a fluorinated backbone to as high as 30% elongation for the polymer containing an alkoxy-appended backbone.…”
Section: Materials Advancesmentioning
confidence: 99%
“…Stretchable polymer semiconductors are a key component of highly deformable electronics, such as stretchable organic thin film transistors (OTFTs), , for applications in wearable and implantable devices. Common polymer semiconductors, that is, conjugated polymers (CPs), tend to exhibit brittle fracture behavior with low elongation expressed by small crack onset strain (COS), due to their rigid backbone and semicrystalline microstructure as necessities for efficient charge transport. , Strategies such as reducing backbone regioregularity, , inserting nonconjugation breaker into the backbone, introducing flexible coblocks or side chains, , and dispersing conjugated polymers in elastomer binder have been employed to improve the deformability of CPs to COS over 100%. , For a wider range of application scenes, a large deformability of semiconductor nanofilms with high COS far beyond 100% is actually preferable. , Besides COS, elastic recovery (ER) is another important parameter to evaluate mechanical durability of the semiconductors after multiple strain cycles, as buckles are easily formed to result in device deterioration after strain removal in case of irreversible plastic deformation . As semiconductors are supposed to apply in stretchable electronics as thin films, it is important to understand not only the apparent behaviors supported by stretchable substrates but also the intrinsic mechnical properties in thin film free from substrates. , However, in previous reports, the ER of stretchable semiconductors was measured either in the bulk state or by loading a thin film on relatively thick supportive layer, both unable to mirror the intrinsic ER of thin film satisfactorily.…”
Section: Introductionmentioning
confidence: 99%
“…4−6 Common polymer semiconductors, that is, conjugated polymers (CPs), tend to exhibit brittle fracture behavior with low elongation expressed by small crack onset strain (COS), due to their rigid backbone and semicrystalline microstructure as necessities for efficient charge transport. 7,8 Strategies such as reducing backbone regioregularity, 9,10 inserting nonconjugation breaker into the backbone, 11−13 introducing flexible coblocks 14 or side chains, 15,16 and dispersing conjugated polymers in elastomer binder 17−21 have been employed to improve the deformability of CPs to COS over 100%. 22,23 For a wider range of application scenes, a large deformability of semiconductor nanofilms with high COS far beyond 100% is actually preferable.…”
Section: Introductionmentioning
confidence: 99%